2001
DOI: 10.1192/bjp.178.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Light therapy for seasonal affective disorder in primary care

Abstract: Primary care patients with seasonal affective disorder improve after light therapy, but bright white light is not associated with greater improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Although our meta-analysis showed that exposures to high levels of negative ions was associated with a significant improvement in rated depression severity as measured using SIGH-SAD, a primary metric for both seasonal and non-seasonal depression [4,43-46], and a lack of statistical heterogeneity across study results in the high-density analysis was observed, the findings should be cautiously interpreted. First, this body of work typically did not control for or failed to report on environmental factors affecting exposure including the electric field, air flow, humidity, and temperature.…”
Section: Discussionmentioning
confidence: 77%
“…Although our meta-analysis showed that exposures to high levels of negative ions was associated with a significant improvement in rated depression severity as measured using SIGH-SAD, a primary metric for both seasonal and non-seasonal depression [4,43-46], and a lack of statistical heterogeneity across study results in the high-density analysis was observed, the findings should be cautiously interpreted. First, this body of work typically did not control for or failed to report on environmental factors affecting exposure including the electric field, air flow, humidity, and temperature.…”
Section: Discussionmentioning
confidence: 77%
“…Results range from improved recovery from surgery (Ulrich, 1984;Ulrich, Lunden, & Eltinge, 1993), lowered pain of burn patients (Miller, Hickman, & Lemasters, 1992), enhanced recovery from stress, as measured by lowered blood pressure, muscle tension, skin conductance and self-reported feelings (Hartig & Evans, 1993;Parsons, 1998;Ulrich et al, 1991), reduced depression (Genhart, 1993;Wileman, 2001) and improved sleep (Campbell, 1993;Partonen, 1994). Unfortunately, empirical scientific research on the impact of outdoor spaces-or time spent outdoors-for people with dementia is limited.…”
mentioning
confidence: 99%
“…Although our meta-analysis showed that exposures to high levels of negative ions was associated with a significant improvement in rated depression severity as measured using SIGH-SAD, a primary metric for both seasonal and non-seasonal depression [4,[43][44][45][46], and a lack of statistical heterogeneity across study results in the high-density analysis was observed, the findings should be cautiously interpreted. First, this body of work typically did not control for or failed to report on environmental factors affecting exposure including the electric field, air flow, humidity, and temperature.…”
Section: Discussionmentioning
confidence: 60%